World Class Sustainable Manufacturing: a rational approach for Sustainable Competitive Advantage - Beleya, Prashanth; Murugesan, T. K.; Mukthar, K. P. Jaheer; Shukla, Nidhi (Frontiers in Sustainability, 2025)
The rationale of this empirical study is to identify sustainability assessment constructs in the context of WCSM implementation, which has emerged as a key focus of world class manufacturers striving to achieve Sustainable Competitive Advantage (SCA). This study also intends to identify the critical drivers and barriers toward implementation of WCSM. In order to achieve the study's purpose, the primary data were collected from 143 plant managers and supervisors through structured questionnaires administered at select world class manufacturers in South India based on an area-cum-purposive sampling technique. The survey instrument was exclusively designed to capture sustainability assessment dimensions to examine WCSM implementation and to investigate the impetus of WCSM implementation on the achievement of SCA. The findings of this empirical study revealed that five sustainability assessment constructs are identified with the help of Exploratory Factor Analysis (EFA). They are labeled as “WCSM Practices”, “Environmental Benefit Dimensions”, “Social Benefit Dimensions”, “Economic Benefit Dimensions” and “WCSM Implementation”. These sustainable assessment constructs are regarded as essential by South Indian world class manufacturers for the achievement of sustainable competitive advantage. Moreover, this study also confirmed that the seven key factors which positively influenced the implementation of WCSM are labeled as “WCSM Drivers” and the six key factors which negatively influenced the implementation of WCSM are labeled as “WCSM Barriers”. Finally, the study's findings indicated that the adoption and implementation of WCSM exert a substantial positive influence on achieving sustainable competitive advantage.